Modern C++ programming cookbook : over 100 recipes to help you overcome your difficulties with C++ programming and gain deeper understanding of the working of modern C++ /: over 100 recipes to help you overcome your difficulties with C++ programming and gain deeper understanding of the working of modern C++. (2017) - Bancila, Marius
No abstract available